Oryza genome evolution through a tetraploid lens - Fornasiero, Alice; Feng, Tao; Al-Bader, Noor; Alsantely, Aseel; Mussurova, Saule; Hoang, Nam V.; Misra, Gopal; Zhou, Yong; Fabbian, Leonardo; Mohammed, Nahed; Rivera Serna, Luis; Thimma, Manjula; et al. (Springer, 2025)
Oryza is a remarkable genus comprising 27 species and 11 genome types, with ~3.4-fold genome size variation, that possesses a virtually untapped reservoir of genes that can be used for crop improvement and neodomestication. Here we present 11 chromosome-level assemblies (nine tetraploid, two diploid) in the context of ~15 million years of evolution and show that the core Oryza (sub)genome is only ~200 Mb and largely syntenic, whereas the remaining nuclear fractions (~80–600 Mb) are intermingled, plastic and rapidly evolving. For the halophyte Oryza coarctata, we found that despite detection of gene fractionation in the subgenomes, homoeologous genes were expressed at higher levels in one subgenome over the other in a mosaic form, demonstrating subgenome equivalence. The integration of these 11 new reference genomes with previously published genome datasets provides a nearly complete view of the consequences of evolution for genome diversification across the genus.